Os recursos de linguagem como contribuição à construção de sentido entre formadores e professores em formação em ambientes virtuais - Vizentim, Rosimeire Moreira (2009)
This is a case study that investigates a group of teachers, attendees of the 10th edition of the Distance Learning Training Course for Teachers at Uniso - University of Sorocaba. It intends to understand how the use of visual, verbal and digital languages contributes to the construction of meaning between teacher and learners. The research procedures involved the analysis of documents of the Institutional Educational Project at Uniso, the 10th edition of the Distance Learning Training Course CD-ROM, and interviews with attendees. The results of this study suggest that, despite the difficulties faced by teachers in the use of multimedia languages, the experience has set them to a privileged position in their teaching online training and has enabled the understanding of how to use this educational practice